2004
DOI: 10.2320/matertrans.45.1147
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Bioactive Glass Coatings on Co-Cr Implant Alloys

Abstract: ASilicate glass coatings on Vitallium Ò , a Co-Cr alloy were prepared using a simple enameling technique. The composition of the glasses in the SiO 2 -Na 2 O-K 2 O-MgO-CaO-P 2 O 5 system has been tailored to match the thermal expansion of the alloys. The optimum glass composition and firing conditions (temperature and time) needed to fabricate homogeneous coatings with good adhesion to the alloy were determined. The final coating thickness ranged between 40 and 60 mm. Coatings fired under the optimum condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Initially, there is dissolution of the silicon matrix coating after immersion in SBF. Such dissolutions are reported earlier through pulse laser‐deposited bioactive glass coatings . The mechanism of apatite formation in bioactive glass is described by Hench in four stages, as discussed previously.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Initially, there is dissolution of the silicon matrix coating after immersion in SBF. Such dissolutions are reported earlier through pulse laser‐deposited bioactive glass coatings . The mechanism of apatite formation in bioactive glass is described by Hench in four stages, as discussed previously.…”
Section: Resultssupporting
confidence: 61%
“…Such dissolutions are reported earlier through pulse laser-deposited bioactive glass coatings. [43][44][45][46][47] The mechanism of apatite formation in bioactive glass is described by Hench 8 in four stages, as discussed previously. The increase in apatite formation is evident from the epifluorescence micrographs which show an increase in green fluorescence with exposure time.…”
Section: Wwwceramicsorg/act Nbg Particles On Ti-6al-4v Alloymentioning
confidence: 99%
“…The biodegradable Gel-P-BCP composite material had well defined interconnected pores which facilitates osteoconductivity and promotes cell adhesion, proliferation and viability for bone tissue formation[54].Bioactive glass (BG) scaffolds are interesting candidates currently employed in bone tissue restoration owing to their osteoconductivity, osteoinductivity and bone bonding ability. BGs are generally used as bioactive coating material on orthopedic implants, dental applications, bone filling materials and small bone implants[55][56][57]. In a recent study, selenium (Se) nanoparticles showed a significant role in the modulation of cell proliferation, antioxidant protection and enhanced immune surveillance.…”
mentioning
confidence: 99%
“…It is noteworthy here that typically cracks, poor densification and lack of adhesion can be observed in the bioactive glass coating due to the thermal stress or irregular interparticle spacing problems . The morphology of sol–gel derived bioactive glasses affects their bioactivity, expressed as osteoconductivity, and tissue attachment properties .…”
Section: Introductionmentioning
confidence: 99%
“…This apatite layer being chemically similar with the mineral phase of the natural bone promotes bonding between the bioactive glass and the soft as well as hard tissues of the host . Accordingly, bioactive glass coatings on inert implants (e.g., inert glass reinforced bone implants) facilitate bonding between the implant and the surrounding tissue . Coatings can also help to maintain mechanical durability of the implant for longer period .…”
Section: Introductionmentioning
confidence: 99%